Relationship between toxoplasma IgG avidity levels and abortion risk - Wulandari, Shinta Ayuni (International journal of health sciences, 2024)
Abortion is still a problem that receives special attention because based on data from the World Health Organization (WHO), abortion accounts for 15-50% of the causes of maternal death in the world. One of the risk factors for abortion is infection during pregnancy, including toxoplasmosis. The aim of this study was to analyze whether there was a relationship between toxoplasma IgG avidity levels and the risk of abortion. The research uses a literature review study to identify, analyze, and evaluate scientific papers through MDPI, PubMed, and ScienceDirect data sources. 60 articles were produced from the four data sources, there were 7 articles that passed the inclusion criteria which are summarized in the PRISMA diagram. The results in one article mentioned two abortions and the other article mentioned 17 abortions, both in first trimester pregnant women with low toxoplasma IgG avidity levels. Both articles show the results that women who have low toxoplasma IgG avidity levels experience more abortions in the early trimester than women who have medium or high toxoplasma IgG avidity levels. The conclusion of this study was that there was a relationship between toxoplasma IgG avidity levels and the risk of abortion.